The color of time on the progression of letters: Notes between black and white on the passage from orality to literacy - Fröhlich, Cláudia Bechara; Moschen, Simone (Education Policy Analysis Archives, 2017)
Based on the experience with literacy teachers from Rio Grande do Sul elementary schools, we aim to make visible an apparently invisible thread between time and passage from orality to literacy. As a way of photographing the school daily life and emphasizing different shades of a non-dictionary registered color, the color of time, we combine this reflection with the time of understanding – Lacan’s concept of logical time – lenses to see, which allowed the proposal of the fall of the school’s binary logic of alphabetization or non-alphabetization (as they are studied in Brazil). The welcoming of a ternary logic, a time of passage in which one is simultaneously in the state of alphabetization and non-alphabetization, helps to evidence an ongoing process towards the literate position, an approach that considers the uniqueness and the desire in the process of literacy.